Implementasi Qanun dalam Penertiban Pedagang Kaki Lima di Aceh: Analisis Kesenjangan Implementasi dan Kriminalisasi Tidak Langsung - Maula Sari; Ramadhan Ramadhan (IAIN Langsa, 2026)
This study aims to analyze the implementation of qanun in regulating street vendors in Aceh by highlighting the gap between normative regulatory frameworks and their practical implementation, as well as the potential emergence of indirect criminalization of informal trading activities. This research constitutes field-based research employing a qualitative approach with a socio-legal (juridical-empirical) method. Primary data were obtained through interviews with officials of the Satuan Polisi Pamong Praja, the Department of Industry, Trade, and SMEs, street vendors, and community leaders in Lhokseumawe City and East Aceh Regency, complemented by field observations. Secondary data were derived from relevant qanun regulations as well as related academic literature. The findings indicate that although the Qanun of Lhokseumawe City No. 1 of 2014 and the Qanun of East Aceh Regency No. 11 of 2014 normatively regulate the management and empowerment of street vendors, their implementation continues to face several challenges, including limited business facilities, varying levels of vendor compliance, and inconsistencies in law enforcement. These conditions potentially give rise to indirect criminalization, whereby regulatory enforcement indirectly places street vendors in a vulnerable position to legal sanctions without the provision of adequate alternative trading spaces.